STUDY AND ANALYSIS OF DEVELOPMENT STAGES OF PHYSICAL CULTURE AND SPORT IN THE REPUBLIC OF UZBEKISTAN AFTER INDEPENDENCE - Meyliyev , X.; Tajiboyeva , G. (Educational Research in Universal Sciences, 2023)
This article analyzes the stages of development of physical education and sports in our Republic after independence, information about the achievements and results achieved.